2015
DOI: 10.1016/j.geotexmem.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polypropylene fibres on the compressive and tensile strength of a soft soil, artificially stabilised with binders

Abstract: This work studies the effect of binder and fibre quantity on the mechanical behaviour of "Baixo Mondego" soft soil, chemically stabilised with binders and reinforced/non-reinforced with short polypropylene fibres. The experimental programme was comprised by four types of tests, one to evaluate compressive strength (unconfined compressive strength test) and three to evaluate tensile strength (direct tensile strength test, split tensile strength test and flexural strength test). The results indicate that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(69 citation statements)
references
References 24 publications
3
58
0
5
Order By: Relevance
“…Tests results indicated that stiffness and compression strength of sandy soil, increases with cement and fiber content. Correira et al (2015) studied the effect of binder and polypropylene fiber quantity on the mechanical behavior of soft soil; results reveal that the increment of binder quantity improves the stiffness, the compressive and the tensile strength of the soil; however, the presence of fibers may reduce this beneficial effect.…”
Section: Fiber-reinforced Soilmentioning
confidence: 99%
“…Tests results indicated that stiffness and compression strength of sandy soil, increases with cement and fiber content. Correira et al (2015) studied the effect of binder and polypropylene fiber quantity on the mechanical behavior of soft soil; results reveal that the increment of binder quantity improves the stiffness, the compressive and the tensile strength of the soil; however, the presence of fibers may reduce this beneficial effect.…”
Section: Fiber-reinforced Soilmentioning
confidence: 99%
“…In order to circumvent the durability issue, synthetic polypropylene fibers having durable life span were used (Consoli et al 2011, Correia et al 2015. The wealth of earlier available literature suggests that both fiber characteristics (including fiber orientation, type, length, thickness, dosage and geometry), nature of clay and type of stabilizer affect the resultant behavior of fiber-reinforced clays (Gray 1970, Gray andMaher 1989;Maher and Ho 1994;Consoli et al 2009;Ahmed et al 2010;Zhu et al 2014;Tang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The latter implies that the sample is submitted to a stress state of tension along the vertical plane and fails due to the lack of sufficient tensile strength. As geomaterials usually have a higher compressive strength than tensile strength [35][36][37][38][39][40][41][42][43], it can be expected that the UCSes obtained by axial split failure are lower than those obtained by diagonal shear failure. To ensure safe production and successful application of the backfill, the required strength of the cemented backfill must be adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%